PIDANA BERSYARAT TERHADAP PELAKU TINDAK PIDANA KEKARANTINAAN KESEHATAN (STUDI PUTUSAN NOMOR 21/PID.S/2021/PN TNG): Conditional Punishment for Perpetrators of the Health Quarantine Crimes (A Study of Decision Number 21/Pid.S/2021/Pn Tng) - Muhammad Jafar Shodiq; Dian Adriawan Daeng Tawang (Faculty of Law, Universitas Trisakti, 2025)
In 2020, during the COVID-19 pandemic, Indonesian influencer Rachel Vennya evaded mandatory quarantine after returning from New York by bribing the COVID-19 Task Force. Her case was reviewed under Verdict No. 21/Pid.S/2021/PN.Tng. This study analyzes the imposition of conditional criminal sanctions and the characteristics of the penalties applied. Using a normative-descriptive method with qualitative analysis and deductive reasoning, the research draws from primary and secondary legal sources. Criminal sanctions aim not only to punish violations but also to promote social and psychological compliance, while quarantine rules seek to prevent disease transmission. The findings show that Rachel Vennya and her accomplices received conditional sentences that do not align with substantive justice, as the lenient sanctions fail to reflect the seriousness of the offense. Ideally, the perpetrators should have received stricter penalties or served the four-month imprisonment determined by the court. Thus, law-enforcement authorities, especially judges, must impose proportionate sanctions to strengthen deterrence and uphold legal order.